(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the prevalence of depression and analyze its associated factors among inpatients aged under 60 years with vestibular disorders treated at the Department of Neurology, Bach Mai Hospital. Methodology: The cross-sectional study was conducted on 91 inpatients diagnosed with vestibular disorders at the Department of Neurology, Bach Mai Hospital, from August 2024 to March 2025. The Hamilton Depression Rating Scale (HAM-D) was utilized to classify and assess depression levels among these patients. Results: the prevalence of depression in patients with disorder of vestibular function was 20.9%. Longer disease duration (p<0.01), high frequency of dizziness (p<0.01) and history of vestibular dysfunction (p<0.01) are factors that increase the risk of depression in patients with vestibular dysfunction. Conclusion: The chronicity and dizziness frequency of vestibular dysfunction are significantly associated with depression in affected patients.